Mesenteric Panniculitis (MP) in CT – A Predictor of Malignancy? - Scheer, F.; Spunar, P.; Wiggermann, P.; Wissgott, C.; Andresen, R. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: The exact etiology of mesenteric panniculitis (MP) is still unknown and has been discussed in relation to different causes. The aim of this retrospective study was to evaluate a coherence between MP and malignancy.Materials and Methods: Retrospective analysis of consecutive CT abdomen examinations of 5595 patients in terms of MP over a period of 3 years was performed. To make the diagnosis of MP, three of five typical signs were obligatory: hyperdense mass lesion with intercalated nodules, a “fat-ring sign” or halo sign, a hyperdense pseudocapsule and displacement of bowel loops. The patient cohort (mean age: 64.7 years) consisted of 1974 (35.2 %) patients with histologically confirmed cancer and 3621 patients (64.8 %) without known underlying oncological disease.Results: A total of 143 cases were diagnosed with MP (2.55 %). The average age of patients was 69.9 years with a male to female ratio of 2:1. In this group oncological disease was confirmed in 107 patients (74.8 %). In 36 patients with MP (25.2 %), no malignancy was present. In the group of patients with an underlying oncological disease, the prevalence of MP was 5.42 % and was significantly higher (p < 0.005) than in the patients with MP and without an oncological disease. The highest prevalence of MP (29 cases) was observed in non-Hodgkin lymphoma (22.6 %). The statistically calculated risk of a tumor disease in this collective is about 5 times higher if MP was demonstrated (p < 0.001).Conclusion: Based on the data of the collective, the risk of malignancy is five times higher in the presence of MP than in an inconspicuous mesentery. MP seems to frequently occur with non-Hodgkin lymphoma. MP can be seen on the basis of typical morphological features on the CT image. MP must be differentiated from a wide range of benign and malignant diseases of the mesentery.Key points:• Mesenteric panniculitis can be diagnosed with CT.• In the case of accidentally diagnosed mesenteric panniculitis, a possible malignant cause should be ruled out in the differential diagnosis.Citation Format:• Scheer F, Spunar P, Wiggermann P et al. Mesenteric Panniculitis (MP) in CT – A Predictor of Malignancy?. Fortschr Röntgenstr 2016; 188: 926 – 932
Keywords: abdomen; mesentery; CT spiral